(untitled) (International Journal of Physiology, 2020)
The competition in medical field, unhealthy food and lack of exercise deteriorate the health of student. Yoga is the ancient technique to increase the concentration power, physical and mental well-being. We have done randomized control study on medical students between study and control group. The study group has practice yoga for 4 weeks whereas the control group hasn’t. In the study group there is significantly improvement in cardio-respiratory parameters (p<0.0001).This study showed that regular yoga practice in medical students can decrease their stress and improve cardiac and respiratory function.